Meningioma achieves malignancy and erastin-induced ferroptosis resistance through FOXM1-AURKA-NRF2 axis - Yangfan Ye; Lei Xu; Liuchao Zhang; Pengzhan Zhao; Wanzhi Cai; Guoqiang Fu; Tian Wang; Zeqiang Tao; Wenqian Shi; Wei Gu; Jingming Hu; Guangyao Yuan; et al. (Redox Biology, 2024)
The oncogene Aurora kinase A (AURKA) has been implicated in various tumor, yet its role in meningioma remains unexplored. Recent studies have suggested a potential link between AURKA and ferroptosis, although the underlying mechanisms are unclear. This study presented evidence of AURKA upregulation in high grade meningioma and its ability to enhance malignant characteristics. We identified AURKA as a suppressor of erastin-induced ferroptosis in meningioma. Mechanistically, AURKA directly interacted with and phosphorylated kelch-like ECH-associated protein 1 (KEAP1), thereby activating nuclear factor erythroid 2 related factor 2 (NFE2L2/NRF2) and target genes transcription. Additionally, forkhead box protein M1 (FOXM1) facilitated the transcription of AURKA. Suppression of AURKA, in conjunction with erastin, yields significant enhancements in the prognosis of a murine model of meningioma. Our study elucidates an unidentified mechanism by which AURKA governs ferroptosis, and strongly suggests that the combination of AURKA inhibition and ferroptosis-inducing agents could potentially provide therapeutic benefits for meningioma treatment.